2017
DOI: 10.1016/j.tiv.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiwalled carbon nanotube cytotoxicity in cultures of human brain microvascular endothelial cells grown on plastic or basement membrane

Abstract: There is a growing interest in the use of multiwalled carbon nanotubes (MWCNTs) to treat diseases of the brain. Little is known about the effects of MWCNTs on human brain microvascular endothelial cells (HBMECs), which make up the blood vessels in the brain. In our studies, we evaluate the cytotoxicity of MWCNTs and acid oxidized MWNCTs, with or without a phospholipid-polyethylene glycol coating. We determined the cytotoxic effects of MWCNTs on both tissue-mimicking cultures of HBMECs grown on basement membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…48 Hence, surface functionalization enables a proper way to reduce the cytotoxicity of CNTs through effective cellular uptake processes. 49 In addition, functionalization of CNTs directly affects cellular uptake quality and the cellular internalization mechanisms mentioned above. In Table 4, functionalized CNTs and their effect on solubility, toxicity, effective cellular internalization mechanisms, etc.…”
Section: Functionalizationmentioning
confidence: 99%
“…48 Hence, surface functionalization enables a proper way to reduce the cytotoxicity of CNTs through effective cellular uptake processes. 49 In addition, functionalization of CNTs directly affects cellular uptake quality and the cellular internalization mechanisms mentioned above. In Table 4, functionalized CNTs and their effect on solubility, toxicity, effective cellular internalization mechanisms, etc.…”
Section: Functionalizationmentioning
confidence: 99%
“…An additional confounding factor in assessment of the toxic effects of nanomaterials, including AgNPs, is that they can interfere with assays reliant upon optical absorbance, fluorescence, or luminescence measurements [ 48 51 ]. Nanoparticles themselves could absorb or scatter light, fluoresce, or increase autofluorescence in cells.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for nanoparticles to affect background absorbance or fluorescence measurements in part can be accounted for by subtracting background measurements taken from label-free, nanoparticle treated cells as we have done in the studies reported here. Nanoparticles also may increase or quench fluorescence from certain fluorophores, quench luminescence, or potentially affect the reaction rates for formation of substrates used to assess cell viability [ 48 51 ]. Because these types of interference are challenging to assess under experimental conditions used for cell-based assays, cell-free systems commonly are used.…”
Section: Discussionmentioning
confidence: 99%
“…They report that oxidized soot was more cytotoxic than untreated, but did not differ in its induction of IL-8 secretion. In contrast, Eldridge et al evaluated toxicity by exposing the microvascular endothelial cells with short and thin MWCNT, with or without oxidation treatment and with or without phospholipid-polyethylene glycol (PL-PEG) coating [58]. They reported that coated MWCNT was cytotoxic, with greater toxicity from untreated MWCNT, whereas uncoated MWCNT was not cytotoxic with or without oxidation treatment.…”
Section: Discussionmentioning
confidence: 99%